Relational Reasoning in Tertiary Education: What Is Its Value and How Can It Be Assessed and Trained? - Alexander, Patricia A.; Gans, Nancy; Maki, Alina J. K. (Frontiers in Education, 2022)
The goal of this article is to demonstrate the value of incorporating relational reasoning assessment and training in tertiary education. To accomplish this, the authors organize the article into three sections. The first section overviews the nature of relational reasoning, and its different forms, developmental trajectories, and assessment. How relational reasoning predicts performance in various academic domains and fields of practice is also considered. The second section focuses on the role that relational reasoning plays in the scientific domains that are foundational to tertiary education and professional practice—the natural, social, applied, and formal sciences. In the final section, the authors describe an ongoing design experiment in which relational reasoning assessment and training are integrated into a university course.